Displaced Commercial Risk Pada Bank Syariah (Studi Pada Bank X) - Mustafidah, Wiwit (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this study is to determine how the process of risk management toward displaced commercial risk. This study used a qualitative approach with case study method in the X Islamic Bank. Techniques of data collection was conducted by doing interview and documentation. At the results, X Islamic Bank processing risk management toward displaced commercial risk by doing six stages. First stage was: determination of context by defining comprehension and stakeholders, the second stage was: identification by looking at the cause of the displaced commercial risk, more over: analysis of risk by identifying strategies, impact, and estimate the level of impact measurement, the fourth evaluation of risk by giving the decision process risk, fifth: risk treatment by way of mitigation measures / accept riskthe last stage was : monitor and review by looking at the balance sheet to determine the level of the banks financial stability.